2022
DOI: 10.1016/s0140-6736(21)02392-8
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus no anticoagulation for post-discharge thromboprophylaxis after hospitalisation for COVID-19 (MICHELLE): an open-label, multicentre, randomised, controlled trial

Abstract: Background Patients hospitalised with COVID-19 are at risk for thrombotic events after discharge; the role of extended thromboprophylaxis in this population is unknown. Methods In this open-label, multicentre, randomised trial conducted at 14 centres in Brazil, patients hospitalised with COVID-19 at increased risk for venous thromboembolism (International Medical Prevention Registry on Venous Thromboembolism [IMPROVE] venous thromboembolism [VTE] score of ≥4 or 2–3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
5
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 22 publications
3
157
5
15
Order By: Relevance
“…The COVID-19 pandemic may have led to a reduction in the use of imaging tests for diagnostic workup [8] , [10] . Furthermore, a broader and more aggressive use of pharmacological preventative measures for venous thromboembolism may have partly reduced this risk, as recently shown by trials conducted in the hospital and ambulatory setting [11] , [12] . One nationwide French study illustrated that the number of pulmonary embolism-related hospitalizations and in-hospital fatality increased in 2020, particularly during the COVID-19 waves [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic may have led to a reduction in the use of imaging tests for diagnostic workup [8] , [10] . Furthermore, a broader and more aggressive use of pharmacological preventative measures for venous thromboembolism may have partly reduced this risk, as recently shown by trials conducted in the hospital and ambulatory setting [11] , [12] . One nationwide French study illustrated that the number of pulmonary embolism-related hospitalizations and in-hospital fatality increased in 2020, particularly during the COVID-19 waves [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Coagulopathy in COVID-19 has a wide spectrum of clinical presentations with variable severity ranging from asymptomatic to organ dysfunction and death. From the early period of COVID-19, it has been recognized that venous thromboembolic diseases, including deep venous thrombosis and pulmonary embolism, are very prevalent among acutely ill patients [5]. Further, the coagulopathy complications may include arterial events resulting in a stroke, myocardial infarction, and limb ischemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19 are often treated with heparin during hospitalization to prevent thrombosis. However, the hypercoagulable state often persists after discharge [ 138 , 139 , 140 ], and some reports have suggested that transition to a direct oral anticoagulant (DOAC) at discharge may be useful [ 141 ].…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 99%